Still Ours to Lead : America, Rising Powers, and the Tension between Rivalry and Restraint - Jones, Bruce D. (Book collections on Project MUSE., 2014)
Is the United States still a ""superpower""? How are the rising powers establishing themselves in international politics and security? What is the future of global stability?For over a decade, Bruce Jones has had a front-row seat as the emerging powers-principally China, India, and Brazil, but also Turkey, Indonesia, Korea, and others-thrust themselves onto the global stage. From Delhi to Doha to Beijing to Brasilia, he's met with the politicians, diplomats, business leaders, and scholars of those powers as they craft their strategies for rising influence-and with senior American officials as